Pengaruh Publikasi Laporan Keuangan Terhadap Abnormal Return Emiten Yang Terdaftar Pada Jakarta Islamic Index (JII) Studi Kasus Pada PT Perusahaan Gas Negara (PGAS) - Muhammad Ady Mahfuzh (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
The purpose of this research is to examine the impact of financial report publishing on the abnormal stock price returns of PGAS issuers. The Event study approach was employed in this investigation. This analysis focuses on the second and third t, or 10 days before and 10 days following the release of the third quarter 2021 financial accounts. The information in this study was derived from historical data on the daily stock price movements of PGAS-coded issuers from May to November 2021. The association between financial report publishes and aberrant stock price returns of PGAS issuers is examined using signal theory in this study. This study is to re-examine the link between the influence of financial report publication on abnormal return, as there are still inconsistencies in the financial report publication variable in affecting abnormal return. The findings revealed that financial report publishing had no influence on the average abnormal return on the share price of PGAS issuers.